Information Technologies and Analytics as Decision Support Systems in Hospital Logistics: Four Research Experiences in the Colombian Case (2017)
This article presents four research experiences in hospital logistics using simultaneously mathematical models and information management. The cases analyzed included the efficient scheduling of nursing shifts, kidney exchange programs, the design of medical equipment maintenance policies, and the design of rapid response tools for cardiovascular accidents. The problems found are presented and the technological solutions developed are described. The results obtained show the importance of combining information management and optimization models in the four cases in question. Future work includes the collection of historical data to fine-tune and improve the performance of the solutions developed, and as such to predict the behavior of the logistics systems studied.